Effective Containment of a COVID-19 Subregional Outbreak in Italy Through Strict Quarantine and Rearrangement of Local Health Care Services. (19th January 2021) - Tedeschi, Sara; Badia, Lorenzo; Berveglieri, Fabio; Ferrari, Rodolfo; Coladonato, Simona; Gabrielli, Sabrina; Maestri, Antonio; Peroni, Gabriele; Giannella, Maddalena; Rossi, Andrea; Viale, Pierluigi; ,
Abstract: Background: Since the beginning of the pandemic, the epidemiology of coronavirus disease 2019 (COVID-19) in Italy has been characterized by the occurrence of subnational outbreaks. The World Health Organization recommended building the capacity to rapidly control COVID-19 clusters of cases in order to avoid the spread of the disease. This study describes a subregional outbreak of COVID-19 that occurred in the Emilia Romagna region, Italy, and the intervention undertaken to successfully control it. Methods: Cases of COVID-19 were defined by a positive reverse transcriptase polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on nasopharyngeal swab. The outbreak involved the residential area of a small town, with 10 500 inhabitants in an area of 9 km 2 . After the recognition of the outbreak, local health care authorities implemented strict quarantine and a rearrangement of health care services, consisting of closure of general practitioner outpatient clinics, telephone contact with all residents, activation of health care units to visit at-home patients with symptoms consistent with COVID-19, and a dedicated Infectious Diseases ambulatory unit at the nearest hospital. Results: The outbreak lasted from February 24 to April 6, 2020, involving at least 170 people with a cumulative incidence of 160 cases/10 000 inhabitants; overall, 448 inhabitants of the municipality underwent at least 1 nasopharyngeal swab to detect SARS-CoV-2 (positivity rate, 38%). Ninety-three people presented symptoms before March 11 (pre-intervention period), and 77 presented symptoms during the postintervention period (March 11–April 6). Conclusions: It was possible to control this COVID-19 outbreak by prompt recognition and implementation of a targeted local intervention.